2020
DOI: 10.3390/plants9060727
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroid Content and Therapeutic Activity in Elicited Spinach Accessions

Abstract: While spinach is an established nutritionally important crop, its medicinal value is not as well known. Spinach is rich in ecdysteroids, insect hormone analogs with a number of medicinal properties including anti-oxidative, anti-inflammatory and even anabolic activity. However, the potential of spinach as a medicinal plant has not yet been developed. In this study, the ecdysteroid content of spinach was optimized to increase its therapeutic value. Spinach seeds from various sources were grown under controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
2
17
0
1
Order By: Relevance
“…), and similarly from 17 to 885 µg g −1 dry weight displaying significant variations due to season of harvest, development phase, geographical location, natural environment as well as plant variety. [2][3][4][5][6][7][8][9][10] Abnormally, Grucza et al have reported ecdysterone amount in fresh spinach as 0.1 µg g −1 f.w. [11] The levels of ecdysterone reported in spinach suggest that the normal amount of ecdysterone from spinach in a daily diet is rather low.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), and similarly from 17 to 885 µg g −1 dry weight displaying significant variations due to season of harvest, development phase, geographical location, natural environment as well as plant variety. [2][3][4][5][6][7][8][9][10] Abnormally, Grucza et al have reported ecdysterone amount in fresh spinach as 0.1 µg g −1 f.w. [11] The levels of ecdysterone reported in spinach suggest that the normal amount of ecdysterone from spinach in a daily diet is rather low.…”
Section: Introductionmentioning
confidence: 99%
“…Its ecdysteroid content has already been reported in the 1980s and was widely studied since then. [1][2][3][4] Ecdysterone is the most abundant ecdysteroid found in spinach, together with several minor ecdysteroids such as polypodin B, ecdysone, 2-deoxyecdysterone, and makisterone A. [4][5][6][7] In spinach leaves, the levels of ecdysterone are reported from 4 to 800 µg g −1 fresh weight (f.w.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total phenolic and total anthocyanin contents in red lettuce treated with exogenous abscisic acid were significantly higher than in controls [26]. The content of 20-hydroxyecdysone in spinach seedlings increased from 8.3 to 24.7 µg/g after the treatment by methyl salicylate and reached 17.2 µg/g after treatment by methyl jasmonate [27]. Taking into account information on the effect of exogenous regulators on vegetation and biosynthesis of metabolites of a plant object, it is possible to purposefully change the rates of plants' growth and development, as well as the accumulation of biologically active compounds [28].…”
Section: Introductionmentioning
confidence: 83%
“…In Gossypium hirsutum (cotton), application of 20-HE elevates salinity stress and induces germination rate and seedling growth [ 172 ]. In spinach, various elicitors, such as methyl salicylate and mechanical damage, facilitate the production of PEs, which remarkably induce metabolic and anabolic activity in plants [ 199 ]. PEs alleviate salt stress in wheat seedlings by increasing the activity of antioxidants such as catalase, peroxidase, and SOD and the contents of ascorbic acid and glutathione, which reduce ROS and MDA content and promote wheat tolerance to salinity [ 200 ].…”
Section: Role Of Phytoecdysteroids In Stressmentioning
confidence: 99%